MiR-204 regulates type 1 IP3R to control vascular smooth muscle cell contractility and blood pressure. (June 2019) - Gabani, Mohanad; Liu, Jing; Ait-Aissa, Karima; Koval, Olha; Kim, Young-Rae; Castañeda, Diana; Vikram, Ajit; Jacobs, Julia S.; Grumbach, Isabella; Trebak, Mohamed; Irani, Kaikobad; Kassan, Modar
Graphical abstract: Highlights: miR-204 selectively target IP3R1in vascular smooth muscle cells. miR-204 regulates calcium release from the endoplasmic reticulum. miR-204 controls vascular smooth muscle cells contractility. miR-204 plays an important role in regulating blood pressure. Abstract: MiR-204 is expressed in vascular smooth muscle cells (VSMC). However, its role in VSMC contraction is not known. We determined if miR-204 controls VSMC contractility and blood pressure through regulation of sarcoplasmic reticulum (SR) calcium (Ca 2+ ) release. Systolic blood pressure (SBP) and vasoreactivity to VSMC contractile agonists (phenylephrine (PE), thromboxane analogue (U46619), endothelin-1 (ET-1), angiotensin-II (Ang II) and norepinephrine (NE) were compared in aortas and mesenteric resistance arteries (MRA) from miR-204 −/− mice and wildtype mice (WT). There was no difference in basal systolic blood pressure (SBP) between the two genotypes; however, hypertensive response to Ang II was significantly greater in miR-204 −/− mice compared to WT mice. Aortas and MRA of miR-204 −/− mice had heightened contractility to all VSMC agonists. In silico algorithms predicted the type 1 Inositol 1, 4, 5-trisphosphate receptor (IP3 R1) as a target of miR-204. Aortas and MRA of miR-204 −/− mice had higher expression of IP3 R1 compared to WT mice. Difference in agonist-induced vasoconstriction between miR-204 −/− and WT mice was abolished with pharmacologic inhibition of IP3 R1. Furthermore, Ang II-induced aortic IP3 R1 was greater in miR-204 −/− mice compared to WT mice. In addition, difference in aortic vasoconstriction to VSMC agonists between miR-204 −/− and WT mice persisted after Ang II infusion. Inhibition of miR-204 in VSMC in vitro increased IP3 R1, and boosted SR Ca 2+ release in response to PE, while overexpression of miR-204 downregulated IP3 R1. Finally, a sequence-specific nucleotide blocker that targets the miR-204-IP3 R1 interaction rescued miR-204-induced downregulation of IP3 R1. We conclude that miR-204 controls VSMC contractility and blood pressure through IP3 R1-dependent regulation of SR calcium release.